THE WEAKEN STATE SOVEREIGNTY AGAINST LIBERALISM AND “HUMAN RIGHTS” - M. Serkan TAFLIOĞLU (Fırat University, 2019)
State which represents the supreme political authority within determined borders, has this power due to the sovereignty over the polulation. Sovereignty right is the core idea that founded the state in the history of the political thought. In real sense, if a state does not have possession of sovereignty right or does not have ability to use it, that political structure is not a state. Liberal thought claims absolute rights belong to human rather than state. The main thesis is existence of human and society prior to state and invented it. In theoric sense, being absolute of sovereignty has began to transform in recent years. Human factor and Human Rights has become superior to sovereignty right in international law. In our study we try to set forth todays understanding of sovereignty due to the history of political thought.